#TITLE_ALTERNATIVE# - FEDRICHSON (NIM : 12212054), GABRIEL
Gas lift method is a useful method to artificially lift well with high density and viscous oil. Mixing gas injection to the formation fluid will reduce formation fluid density, and since the fluid has become lighter the oil will be easier to flow. Heavy oil has a relatively high cloud point. Several production problem will rise if the oil meet its cloud point while flowing in tubing. Because of that, it is imperative to ensure the fluid temperature inside the tubing always above cloud point. Nowadays, electric thermal tool is a common way to handle problem due to cloud point in tubing. Due to heavy oil well usually lifted using gas lift method, this study propose a different approach to cope with this problem. The method is heating the injected gas lift from the surface. When gas mixed with formation fluid at injection point, the mixed fluid temperature will rise. Temperature distribution inside the tubing is calculated by using Hasan-KabirÃ‚Â’s equation and will be checked with cloud point data.